Needs analysis for public green spaces in Grosuplje - Klara Sulič (Urbani Izziv, 2008)
A huge increase in residential and business-commercial construction has characterised Grosuplje, a young town and suburban settlement of the greater Ljubljana area, over the last two decades, thereby increasing the number of possible users of its open space. The arrangement of this settlement development to date has not been successfully followed and urban green areas undergoing the urbanisation process were not treated fully or equivalently to other spatial utilisation. Based on these departure points, a basic question has arisen: what types and quantities of planned green areas are needed in Grosuplje today? It was assumed that such planned areas which would effectively serve the needs of users were lacking in the town, yet doubt regarding accessibility and the public nature of existing green areas has arisen, which could pose a considerable obstacle to users. In order to verify these assumptions and departure points, a short research survey was carried out with the residents, with a spatial analysis performed simultaneously. There were two key findings. The problem of urban green areas and open spaces is more about the quality of the arrangement and content of these spaces rather than the quantity. The need for planned green areas was expressed by the residents of both single homes and multi-storey dwellings. General guidelines for planning green areas in Grosuplje as well as guidelines which could aid in designing the town's appearance were given based on these findings.